Optimalisasi Soft Skill Mahasiswa Akuntansi Universitas Bina Nusantara Melalui Effective Team Building: Pendekatan Eksperimental - Noviyanti Noviyanti; Gatot Soepriyanto (Binus Business Review, 2010)
This study aim's to analyze the differences the methods of team forming between team members selected by their own without intervention from the lecturer, the team members selected by the students themselves with the intervention from lecturer for the next phase (McGrath's model input phase), and designed team by lecturers with McGrath's model application, the establishment of this method's to determine the most effective team. Research methodology used in this study is an experimental method that targeted students who are majoring in accounting through the course of Accounting Theory and Accounting Non-Profit in the whole semester 2008/2009 in Bina Nusantara University. The statistical methods employed are simple correlation, ANOVA, Welch, Brown-Forsythe and Tamhane's T. Our research find that the most effective method is the method of team forming with the application by lecturers with McGrath's model, because the quality of the team performance leads the team into the formation of the same stage with other methods, but is able to reach the highest assignment values than other methods. In addition, the most important in forming an effective team is the quality of various inputs that will be included in the team. McGrath's application model provides the opportunity for the students to be able to work with different partners, who may not know very close each other. Therefore this method can optimize student soft skills in teamwork.